Spatial Variation of Silt and Clay Sediment Deposit in Bhaktapur City - Kawan, Chandra Kiran; Maskey, Prem Nath; Motra, Gokarna (Journal of Science and Engineering, 2019)
3D geological subsurface model of the Bhaktapur City is prepared using RockWork2016, which is based on 3-D Geo-scientific information system (3-D GSIS). The main aim of this study is to interpret the geological conditions of Bhaktapur city, providing subsurface geological database and its relevance to 2015 Gorkha earthquake damages. For this, the borehole data are collected from different sources and digitized in the RockWork2016 program for the generation of the 3-D attributed subsurface model. For the stratigraphy divisions of the soil, the unified soil classification system is used. From the interpretation of the developed attributed model, it is found that the central part or the core area of the Bhaktapur city has a deeper depth of the soft sediment-silt and clay rather than other surrounding parts of the city. This indicates the possibility of local soil amplification in the central part of the study area. The spatial variation of the subsurface sediment deposit is then co-relate with damage scenario caused by 2015 Gorkha earthquake.